A Two-stage Malware Detection Architecture Inspired by Human Immune System - Salah M.A.F.; Sulaiman R.; Mohd Fadzli Marhusin (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by SCOPUS